SISTEM REKOMENDASI MAKANAN TIO CIU MENGGUNAKAN COLLABORATIVE FILTERING - halim, philip bryan; Herwindiati, Dyah Erny; Lauro, Manatap Dolok (Faculty of Information Technology, Universitas Tarumanagara, 2022)
With the advancement of technological innovation, people can order any kind of food easily and this impacts the culinary industries. As people became aware of any kind of foods available to be ordered, people began to eat a different kinds of food varieties. One kind of food variety available to be ordered is the tio ciu food. Therefore, an information system program was designed that can be used by people who like to eat tio ciu foods to be able to get another tio ciu food recommendation so that they can find out more about tio ciu foods that they haven’t eaten yet. The design of this program applies the Collaborative Filtering method. Based on the test, Collaborative Filtering can give user a food recommendation based on their rating beforehand.